REDESIGN UI/UX PADA APLIKASI BCA MOBILE MENGGUNAKAN METODE LEAN UX - Winardi, Michelle; Muawwal, Ahyar; Renny (KHARISMA Tech, 2024)
BCA Mobile is a mobile banking application from PT Bank Central Asia Tbk. which enables customers to perform various types of banking transactions digitally. UI/UX plays an important role in the success of an application because good design can create a positive user experience and increase user satisfaction using the application. The results of observations collected through the rating and review columns on the Play Store and App Store show several problems experienced by users related to the UI/UX of the BCA Mobile application, as well as the results of usability testing from distributing the system usability scale (SUS) questionnaire before redesign to 30 respondents getting a score of 55.85 with an "OK" rating. This study aims to redesign the UI/UX of the BCA Mobile application and produce a new design that can improve user experience and satisfaction. The redesign uses the Lean UX method by going through 4 processes, namely Declare Assumptions, Create an MVP, Run an Experiment, Feedback, and Research. The results of the SUS score after the redesign showed an increase in the score to 83.48 with an "Excellent" rating. So it can be concluded that redesign using the Lean UX method, can create a display that meets user needs and expectations, as well as improves user experience and satisfaction.